2013
DOI: 10.1007/s10616-013-9634-7
|View full text |Cite
|
Sign up to set email alerts
|

Anti-apoptotic mechanism of Bacoside rich extract against reactive nitrogen species induced activation of iNOS/Bax/caspase 3 mediated apoptosis in L132 cell line

Abstract: Nitric oxide is a highly reactive free radical gas that reacts with a wide range of biomolecules to produce reactive nitrogen species and exerts nitrative stress. Bacopa monniera is a traditional folk and ayurvedic medicine known to alleviate a variety of disorders. Aim of the present study is to evaluate the protective propensity of Bacopa monniera extract (BME) through its oxido-nitrosative and anti-apoptotic mechanism to attenuate sodium nitroprusside (SNP)-induced apoptosis in a human embryonic lung epithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 55 publications
0
12
0
Order By: Relevance
“…Moreover, increases in the intensity of Rh‐123 in different cells, post treatment with bacoside, were also observed indicating its ability to restore mitochondrial membrane potential. Role of bacoside A and its components on restoring mitochondrial membrane potential (MMP) is scantily documented . The study is even more important in the light of significance of bacoside A and its components and absence of any detailed analysis on the role of individual bacoside in regulating MMP.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Moreover, increases in the intensity of Rh‐123 in different cells, post treatment with bacoside, were also observed indicating its ability to restore mitochondrial membrane potential. Role of bacoside A and its components on restoring mitochondrial membrane potential (MMP) is scantily documented . The study is even more important in the light of significance of bacoside A and its components and absence of any detailed analysis on the role of individual bacoside in regulating MMP.…”
Section: Discussionmentioning
confidence: 99%
“…Amongst four individual bacoside and their mixture, bacoside A3 and bacopaside II have shown around 2‐fold increased cell viability compare with stressed cells (Figure ). Previous studies have reported cytoprotective activity of bacosides rich extract against H 2 O 2 ‐induced cell mortality . Collectively, this study suggests that bacoside A components and bacoside mixture may be used as a neuroprotective compound with optimized dose having bacoside of specified concentration.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations